Increasing Customers In Craft Businesses Post Covid-19 Pandemic With E-Prospects - Hastuti, Indra; Purnomo, Singgih; Thi Thu Hang, Nguyen; Sopingi, Sopingi (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
After the Covid pandemic, the digitalization era has developed more rapidly. The E-Prospects-based entrepreneurship development model can be an alternative for the recovery of business actors to increase customers and increase profits so that business actors can recover more quickly and develop. This research aims to analyze the implementation of the E-Prospect application towards increasing customers in Craft Businesses after the Covid-19 Pandemic. The results of this research can be used as a model for developing Craft Businesses to get new customers more quickly and increase profits. This research was carried out with a descriptive research approach, using the case study method on Lintang Kejora Solo crafts and action research and explanatory research, then carrying out educational actions on E-Prospects and Digital Marketing as well as analyzing the increase in profits obtained and continuing with observation actions on the use of E information technology -Prospects as a means of managing prospective customers so that customer retention increases and ends with analyzing the development of the Lintang Kejora craft business in terms of number of customers, turnover and profit. The research results show that after the Lintang Kejora craft business used the website-based E-Prospek application, the increase in customers was 35% and the profit increase rate was 25%. E-Prospect can improve digital-based customer relationship management and can help craft businesses recover after the Covid-19 pandemic.